Elaboration and characterization of a meat sausage based on sable fish (trichiurus lepturus) (@limentech, Ciencia y Tecnología Alimentaria, 2022)
The sablefish (Trichiurus lepturus) is a semi-fatty fish, with an important content of proteins, minerals and different vitamins.The objective of this study was to elaborate and evaluate the physicochemical, microbiological, sensory and texture characteristics of a sausage from sable meat (Trichiurus lepturus), with olive oil as a source of omega 3. The proximal composition was determined following the AOAC (2012) methods.The microbiological characteristics were determined according to Colombian Technical Standards 4458. Acceptability was evaluated by a panel of untrained judges, using a hedonic scale of 4 descriptors (taste, color, odor and texture). Three formulations identified as (F1), (F2), (F3) and a control sample were tested. Significant differences (p
Keywords: fatty acids; fish flour; meat sausage; protein